Dynamics of Peripheral Blood T-lymphocytes Have Predictive Values for the Clinical Outcome of COVID-19 Patients in Intensive Care Unit - Dongling Wu; Xinmin Zhang; Yonah Ziemba; Nina Haghi; Judith Brody; Peihong Hsu (SAGE Publishing, 2022)
Background: Coronavirus disease 2019 (COVID-19) patients with severe disease had a high mortality rate. It's imperative to identify risk factors associated with disease progression and prognosis. Immune responses played an important role in the host's defense against the virus. We studied the dynamics of peripheral blood lymphocytes (PBLs) in relation to the clinical outcome in COVID-19 patients in intensive care unit (ICU). Design: This cohort included 342 COVID-19 patients who were admitted to ICU between February 1 and May 30, 2020, with 178 having follow-up PBL analysis. The patients were divided into a group that survived and an expired group. PBL analysis was performed by flow cytometry. Results: At time of initial flow analysis, there were no statistically significant differences in lymphocyte, T-cell and subsets, B-cell or natural killer (NK) cell counts between the 2 groups. However, during the ICU course, the surviving group demonstrated a full recovery of CD3+ T-cells, CD4+ T-cells, and CD8+ T-cells, with no significant change in B-cells, and a slight upward trend in NK-cells. In contrast, the expired group showed no recovery in T-cells (and subsets) and no significant changes in B-cells and NK-cells. We identified the earliest time points and cut-off values for T-cell subsets that predict clinical outcomes. Conclusion: The results of this study suggest that evaluation of PBL in COVID-19 patients could be valuable in the study of the immune responses to the disease and the prognostication of outcome.